Sustainable and risk-resilient circular supply chain: A Peruvian paint manufacturing supply chain model - Vidal, Ulrich (2024)
The article aims to propose a comprehensive approach to sustainable practices and risk resilience in a circular economy within the supply chain of a manufacturing company, addressing current challenges in sustainability, risk, and resilience. The interconnectedness of these aspects with the circular economy in the supply chain context is emphasized. The study employs fuzzy DEMATEL and fuzzy AHP tools in its design to address sustainable practices, risk resilience, and the circular economy in the manufacturing company's supply chain. Fuzzy logic facilitates the management of imprecision and uncertainty, allowing for a flexible and precise evaluation. Fuzzy AHP focuses on ambiguous and subjective criteria, while fuzzy DEMATEL aids in understanding causal relationships among criteria, considering their fuzzy nature and interdependencies. Findings indicate that Supplier 1, Manufacturer 2, and Distributor 1 are the optimal choices, while efficiency (CSC1), security (RR3), and other criteria are identified as the most influential factors. The uniqueness of the study lies in its specific application and adaptation to the paint manufacturing supply chain sector, with a focus on sustainability, resilience, and the circular economy. The distinctive contribution involves customizing established methodologies to address sector-specific challenges, providing a practical tool for strategic decision-making. By applying an integrated approach based on fuzzy DEMATEL and fuzzy AHP techniques to the Peruvian painting company, the study offers a valuable perspective on the criteria for significant improvements in management, promoting sustainability, and the circular economy at the local level.